GAMBARAN TINGKAT PENGETAHUAN TENAGA KERJA PT’X’ TENTANG UNDANG-UNDANG DAN PERATURAN KESEHATAN DAN KESELAMATAN KERJA - Andi Hendrawan (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Work safety has been a concern in government and business for a long time. Occupational safety factors are important because they are closely related to employee performance and in turn to company performance. The increasing availability of work safety facilities the less likely the occurrence of work accidents. Metpde used in this research is metodesurvey with approach of cross sectional.sampelyang used as many as 40 people with total sampling technique, Samples are asked to fill questionnaires distributed by researcher then collected and processed with statitik diskripttif. The results showed 10 samples have a good level of knowledge, 25 samples of sufficient knowledge level and 5 samples of knowledge level of bad.